Pelaksanaan Bimbingan Penyuluh Agama Islam Kepada Masyarakat Dengan Menggunakan Bahasa Agama Di Kabupaten Langkat - Wahyu Ziaulhaq (PT FORMOSA CENDEKIA GLOBAL, 2022)
This article aims to describe the implementation of guidance for Islamic religious instructors to the community using religious language in Langkat Regency. Allah SWT. The type of writing this article is a qualitative service that seeks to describe and describe the sincere and sincere service of Islamic religious educators to the community which has been carried out and then described in a structured manner by following the rules of writing scientific papers that apply. From the results of writing this article, it is found that: First, the implementation of counseling guidance is carried out in the community andin several cross-sectoral institutions/institutions. Second, Islamic religious inst-ructors have clear work goals and measurable work programs. Third, the implementation of guidance is carried out in a humanistic and persuasive manner.